2002
DOI: 10.1152/ajpendo.00474.2001
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of insulin secretion by phorbol esters is mediated by PKC-α and nPKC isoforms

Abstract: Culturing clonal β-cells (HIT-T15) overnight in the presence of phorbol ester [phorbol myristate acetate (PMA)] enhanced insulin secretion while causing downregulation of some protein kinase C (PKC) isoforms and most PKC activity. We show here that this enhanced secretion required the retention of PMA in the cell. Hence, it could not be because of long-lived phosphorylation of cellular substrates by the isoforms that were downregulated, namely PKC-α, -βII, and -ε, but could be because of the continued activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 34 publications
5
39
1
Order By: Relevance
“…It is of interest to note that the present data on PKC down-regulation in BRIN-BD11 cells stand in contrast to those of Yaney et al (2002) who reported that this isoform was retained in HIT-T15 -cells during long-term PMA treatment. The reasons for this difference are unclear but may relate to the finding that, unlike other isoforms of PKC, PKC requires PMA-induced hyperphosphorylation for down-regulation (Srivastava et al 2002).…”
Section: Discussioncontrasting
confidence: 99%
“…It is of interest to note that the present data on PKC down-regulation in BRIN-BD11 cells stand in contrast to those of Yaney et al (2002) who reported that this isoform was retained in HIT-T15 -cells during long-term PMA treatment. The reasons for this difference are unclear but may relate to the finding that, unlike other isoforms of PKC, PKC requires PMA-induced hyperphosphorylation for down-regulation (Srivastava et al 2002).…”
Section: Discussioncontrasting
confidence: 99%
“…In line with this result is a report showing the blocking of NEFA-stimulated secretion by inhibitors of cPKC and nPKC isoforms in perifused rat islets [147]. In addition, we have shown that KCl-induced insulin secretion was also enhanced after PMA downregulation [140,146]). This would suggest that an increased sensitivity of exocytosis to Ca 2+ and/or an increase in the ready releasable pool of secretory granules was due to an increased vesicle priming or to the prior inhibition of exocytosis.…”
Section: Modulation Of Protein Kinase C Isoforms In the Beta Cellsupporting
confidence: 89%
“…Glucose causes a rise in DAG [24,30,142] and promotes the translocation of PKC-α in the beta cell [143,144,145]. This is consistent with the observation that the mass of PKC-α correlates with the ability of phorbol myristate acetate (PMA), a high affinity surrogate for DAG, to stimulate secretion [146]. Therefore, the short-term activation of PKC is thought to be a positive signal for insulin secretion as seen by the effects of either phorbol esters or cell permeant diacylglycerols.…”
Section: Modulation Of Protein Kinase C Isoforms In the Beta Cellsupporting
confidence: 68%
“…Prolonged stimulation with phorbol esters results in down-regulation of some PKC isoforms (Yaney et al, 2002). When BEAS-2B cells were pre-incubated with PMA (50 ng/ml) for 18 h and then stimulated with PMA, MMP-9 induction was significantly reduced (Figure 2A).…”
Section: Pma Induces Mmp-9 Expression In Beas-2b Cellsmentioning
confidence: 99%